EFEK 2-METHOXYETHANOL TERHADAP STRUKTUR HISTOLOGI TESTIS MENCIT (Mus musculus) - Alifah Hayati; Binti Yunaida; I.B. Rai Pidada; Win Darmanto; Dwi Winarni (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
This research has done to investigate the effect of 2-Methoxyethanol on the testicular histology of the male mice and also the influence the length of time after administration 2-ME stopped in the recovery of the spermatogenic cells and the diameter also the thicknes of seminiferous tubule. Thirty BALB/C male mice 8–9 week old, weighed 28–30 grams body weight. Those mice separated to 6 groups with 5 male mice each group. Those mice were treated with 2-ME 200 mg/kg body weight daily by intra peritoneal injection, within 3 weeks (K1). To investigate the influence the length of time after administration 2-ME stopped, the male mice after treated by 2-ME in 3 weeks also given by the length of time after 2-ME administration stopped 1, 2, 3 and 4 weeks (P1, P2, P3 and P4). The control animal given by intraperitoneal administration of saline. Histological observation was performed on the number of spermatogonium, primary spermatocyte, oval spermatid and the diameter also epithelial thickness of seminiferous tubules. The data were analyzed by One-Sample T-test to investigate the differences between K0 and K1. One Way ANOVA to investigate the influence the length of time after 2-ME administration stopped in the P1, P2, P3 and P4 and then continuing by LSD (Least Significant Difference) to show the differences groups of treatment. The result showed that administration 2-ME could destroy the seminiferous tubules in the testes. Its presented by the decreasing of the number spermatogonium, primary spermatocyte, oval spermatid and diameter also epithelial thickness of seminiferous tubule. The length of time after administration 2-ME stopped could recover seminiferous tubules condition. Its presented by the increasing of the number spermatogonium, primary spermatocyte, oval spermatid, and diameter also epithelial tickness of seminiferous tubules. The conclution of this research were, 2-ME could destroy the testicular histology of the male mice and the length of time after administration 2-ME stopped have linear correlation with seminiferous tubules recovery.